The impact of COVID-19 on Oral and Maxillofacial Surgery patient presentations to the emergency department: A West of Ireland experience - Donohoe, E. (Advances in Oral and Maxillofacial Surgery, 2021)
Following the outbreak of COVID-19 and subsequent restrictions in the Republic of Ireland, the number of Emergency Department attendances have reduced nationally. Concurrently, it would be expected that there would be a reduction in the number of patients attending the emergency department with specific oral and maxillofacial concerns. A retrospective analysis of Oral and Maxillofacial patients attending the Emergency Department in University Hospital Galway during the first three-month period of COVID-19 lockdown in 2020 was compared to patients presenting to the Emergency Department during the equivalent period in the preceding year. The analysis confirmed a 46% reduction in attendances during the COVID-19 lockdown period. There was also a significant decrease in the number of young patients attending due to maxillofacial trauma. Contributing factors to this reduction may include working from home, reducing face-to-face social activities and the closure of social settings. It must be noted that there was a two-fold increase in the number of patients attending with dental pain during the lockdown period in comparison to the preceding year. Similarly, there was a proportional increase in the number of those attending due to infection and requiring subsequent admission during the COVID-19 lockdown period. Patient anxiety related to contracting the virus may have contributed to patients presenting with infection during the COVID-19 lockdown period.